2018
DOI: 10.3892/etm.2018.6248
|View full text |Cite
|
Sign up to set email alerts
|

Application value of expansive pedicle screw in the lumbar short‑segment fixation and fusion for osteoporosis patients

Abstract: Clinical value of expansive pedicle screw in lumbar short-segment fixation and fusion for patients with osteoporosis was investigated. A total of 80 patients with lumbar compression fracture but without obvious nerve compression were selected and divided into the observation group (n=40) and the control group (n=40) using a random number table. The observation group used the expansive pedicle screw, and the control group received conventional pedicle screw fixation and bone graft fusion. In the observation gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Pedicle screw type. Data from 2 studies [50,52] suggested that there was a higher risk of fusion failure with CPS fixation than with expandable pedicle screw (EPS) fixation (OR, 4.77; 95% CI, 2.23 to 10.20; I 2 = 47.5%) (Fig 8). We used the trim-and-fill method to adjust the publication bias, and the OR corrected for publication bias was 2.98 (95% CI, 1.56 to 5.81), which was essentially in line with our results (S6 Table ).…”
Section: Plos Onementioning
confidence: 99%
“…Pedicle screw type. Data from 2 studies [50,52] suggested that there was a higher risk of fusion failure with CPS fixation than with expandable pedicle screw (EPS) fixation (OR, 4.77; 95% CI, 2.23 to 10.20; I 2 = 47.5%) (Fig 8). We used the trim-and-fill method to adjust the publication bias, and the OR corrected for publication bias was 2.98 (95% CI, 1.56 to 5.81), which was essentially in line with our results (S6 Table ).…”
Section: Plos Onementioning
confidence: 99%
“…Owing to the fragile characteristics of the elderly, complications, including screw-loosening events, pseudarthroses, and adjacent kyphosis resulting from compression fractures, may occur after spinal surgery in osteoporosis patients [ 1 ]. In spinal fixation and fusion surgery, screw-loosening events continue to remain a major complication [ 2 ], and cage subsidence is relevant to the severity of osteoporosis [ 3 ]. Recently, adjacent vertebral compression fractures have attracted attention after spinal fixation and fusion in osteoporosis patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Longer instrumented extending to the adjacent segment may lead to several complications such as proximal junctional kyphosis that undermine the effectiveness of surgery[ 1 , 2 ]. To enhance the anchoring strength, several techniques have been used, including bicortical screws, tricortical screws, expandable screws, iliac screws, and iliosacral screws[ 3 , 4 ]. While it is not recommended to extend the extra fixation segment, the strength of bicortical or tricortical screws are also limited and may lead to internal fixation failure in an osteoporotic patients[ 5 ].…”
Section: Introductionmentioning
confidence: 99%